2017
DOI: 10.1002/2017gl072615
|View full text |Cite
|
Sign up to set email alerts
|

Recent changes (2004–2016) of temperature and salinity in the Mediterranean outflow

Abstract: Temperature and salinity series near the seafloor at Espartel Sill (Strait of Gibraltar) have been used to analyze the thermohaline variability of the Mediterranean outflow. The series shows temperature drops by the end of most winters/early springs, which are the remote response to Western Mediterranean Deep Water (WMDW) formation events in the Gulf of Lion that uplift old WMDW nearby the strait. This process distorts the seasonal cycle of colder/warmer water flowing out in summer/winter likely linked to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 59 publications
2
18
0
Order By: Relevance
“…From these diagrams it is possible to note how the Western Mediterranean Transition has changed the basic structure and the properties of the deep layers in the western basin. Over time, these waters eventually spread westward to flow out through the Strait of Gibraltar towards the Atlantic Ocean (Figure 2.3.1), as has been detected by a monitoring site at the sill where the characteristics of the outflowing waters in years 2015-2016 are consistently saltier and warmer than in 2005(Naranjo et al 2017.…”
Section: Mediterranean Deep and Intermediate Water Mass Propertiesmentioning
confidence: 65%
“…From these diagrams it is possible to note how the Western Mediterranean Transition has changed the basic structure and the properties of the deep layers in the western basin. Over time, these waters eventually spread westward to flow out through the Strait of Gibraltar towards the Atlantic Ocean (Figure 2.3.1), as has been detected by a monitoring site at the sill where the characteristics of the outflowing waters in years 2015-2016 are consistently saltier and warmer than in 2005(Naranjo et al 2017.…”
Section: Mediterranean Deep and Intermediate Water Mass Propertiesmentioning
confidence: 65%
“…And it did in an order of magnitude with regards to the before-2012 value! Although this pattern was anticipated in Naranjo et al (2017), they could not give definitive ratification as they used a correspondingly shorter length of this time series (up to year 2015). The extended series available nowadays does confirm the existence of that trend, which is so large and unexpected that has motivated the present study.…”
Section: Water Properties Of the Outflow At The Monitoring Stationmentioning
confidence: 93%
“…Conventional numerical filtering is not advisable to remove these fluctuations because the low-passed series smooths out the footprint of the coldest samples, which are particularly relevant since they inform about the deepest waters that are leaving the MedSea. A possibility of removing tidal fluctuations without losing this information is to extract the coldest sample in each semi-diurnal tidal cycle and decimate the series to a sample per cycle (García Lafuente et al, 2007;Naranjo et al, 2012Naranjo et al, , 2017. Light-blue dots in Figure 3 show the resulting series where most semidiurnal and diurnal tidal variability has been removed.…”
Section: Water Properties Of the Outflow At The Monitoring Stationmentioning
confidence: 99%
“…It also resulted in an anomalous stratification of the deepwater column due to the superposition of newly formed warmer and saltier deep waters . The outflow of these waters through the Strait of Gibraltar is detectable in late winter-early spring (García-Lafuente et al, 2011;Sammartino et al, 2015) and it was clearly identified a decade later (Naranjo et al, 2017). Repeated glider missions along the Ibiza Channel endurance line have provided key semi-continuous observations, from which the variability of the meridional exchanges in the Western basin and its relation to surface and intermediate water mass changes can be monitored (Heslop et al, 2012;Juza et al, 2019).…”
Section: Mediterranean Sea Environmental and Climate Challengesmentioning
confidence: 99%